An Optimal Replenishment Policy for the EPQ Model with Permissible Delay in Payments - Shih-Ming Ou; Kuo-Kuang Chang (Institute of Advanced Engineering and Science, 2016)
Most of the past researches on economic replenishment quantity did not consider the trade credit period. In practice, however, companies in Taiwan have shown that taking the trade credit period into account when they are making inventory decisions decreases costs substantially. The aim of this paper is to develop an inventory model that incorporates a delay in payments to minimize the total inventory-relevant cost. The optimal replenishment policy of the proposed model is identified by utilizing the global optimum conditions and non-constrained quadratic nonlinear programming. The results show that the existence of global optimal inventory cycle under the condition of total cost function is convex. Accordingly, the proposed model can assist managers in effectively addressing EPQ issue under competitive market.